Strengthening Defense Bureaucracy to Enhance the Implementation of Technology-Driven Defense - Sarjito, Aris (Indonesian Journal of Public Administration Review, 2025)
In the rapidly changing defense and security environment, integrating technology into defense bureaucracies presents significant challenges. This study examines these challenges and explores strategies to overcome them, focusing on leadership practices and decentralization to improve efficiency. Utilizing qualitative methods and secondary data, including policy documents and expert analysis, the research identifies key obstacles such as institutional resistance, digital illiteracy, outdated infrastructure, and cybersecurity risks. The study emphasizes the importance of fostering a culture of innovation, upgrading infrastructure, and implementing strong cybersecurity measures. Transformational leadership is highlighted as crucial for driving bureaucratic change and overcoming resistance. Decentralization is also vital, enhancing decision-making by empowering lower-level managers. Effective decentralization requires clear guidelines, communication channels, and technology investments. The findings stress the need for continuous reform and strategic investments to ensure defense bureaucracies are aligned with modern technological demands.